2012
DOI: 10.1016/j.jvs.2011.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound imaging to detect limb stenosis or kinking of endovascular device

Abstract: This large series of DU surveillance for failing EVARs grafts suggests that graft limbs with PSVs <300 cm/s can be safely monitored. However, limbs with more elevated PSVs may benefit from prophylactic intervention or more frequent surveillance to prevent limb occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Of the 17 graft limbs with PSV>300 cm/s, seven developed occlusion and five underwent a prophylactic intervention. The remaining five remained patent over a mean 46 month follow up [5]. We concluded that limb velocities of PSV<300 cm/s and PSV ratio of <3.5 predict for longterm graft limb patency, but they should have continued surveillance.…”
Section: Descriptionmentioning
confidence: 82%
“…Of the 17 graft limbs with PSV>300 cm/s, seven developed occlusion and five underwent a prophylactic intervention. The remaining five remained patent over a mean 46 month follow up [5]. We concluded that limb velocities of PSV<300 cm/s and PSV ratio of <3.5 predict for longterm graft limb patency, but they should have continued surveillance.…”
Section: Descriptionmentioning
confidence: 82%
“…The 22 cohort studies published in full were of mixed quality (Figure 3). 40,41,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] The individual study-level results are detailed in Appendix 6. For the majority of studies, over half or more of the ReBIP criteria were not met, or the information provided in the studies was insufficient to determine if the criteria were met, and were, therefore, judged as being of low or moderate quality.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Information was not available from six studies. 69,71,78,81,82,89 b Per cent of total studies that provided data. Seven studies did not provide data.…”
Section: Study Characteristics Of All Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations